2014
DOI: 10.1002/path.4314
|View full text |Cite
|
Sign up to set email alerts
|

The small heat‐shock protein αB‐crystallin is essential for the nuclear localization of Smad4: impact on pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a devastating disease characterized by the proliferation of myofibroblasts and the accumulation of extracellular matrix (ECM) in the lungs. TGF-β1 is the major profibrotic cytokine involved in IPF and is responsible for myofibroblast proliferation and differentiation and ECM synthesis. αB-crystallin is constitutively expressed in the lungs and is inducible by stress, acts as a chaperone and is known to play a role in cell cytoskeleton architecture homeostasis. The role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 44 publications
(54 reference statements)
5
63
0
Order By: Relevance
“…The authors elucidated the causal role of aB-crystallin in EMT by demonstrating that overexpression of aB-crystallin disrupted monoubiquitination of SMAD4 by interacting with transcriptional intermediary factor 1g, E3eubiquitin ligase and thus limiting its nuclear export. 12,46 Our study in RPE showed that knockdown of aB-crystallin increased the monotetraubiquitination of SMAD4 by threefold and decreased its nuclear localization in both TGF-b2 treated and untreated cells. Interestingly, in RPE, EMT is induced by both TGF-b2, the major TGF-b isoform in the RPE, and BMP4.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…The authors elucidated the causal role of aB-crystallin in EMT by demonstrating that overexpression of aB-crystallin disrupted monoubiquitination of SMAD4 by interacting with transcriptional intermediary factor 1g, E3eubiquitin ligase and thus limiting its nuclear export. 12,46 Our study in RPE showed that knockdown of aB-crystallin increased the monotetraubiquitination of SMAD4 by threefold and decreased its nuclear localization in both TGF-b2 treated and untreated cells. Interestingly, in RPE, EMT is induced by both TGF-b2, the major TGF-b isoform in the RPE, and BMP4.…”
Section: Discussionmentioning
confidence: 82%
“…11, 12 Huang et al 11 showed that aB-crystallin protects 14-3-3z from its degradation by the proteasome leading to the activation of extracellular signaleregulated kinase signaling pathway, which can induce EMT of hepatocellular carcinoma cells. Bellaye et al 12,46 found the overexpression of aB-crystallin in human and rodent fibrotic lung tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations